2021
DOI: 10.1093/dnares/dsab013
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of four novel bacteriophages infecting the clinical pathogen Klebsiella pneumoniae

Abstract: Bacteriophages are an invaluable source of novel genetic diversity. Sequencing of phage genomes can reveal new proteins with potential uses as biotechnological and medical tools, and help unravel the diversity of biological mechanisms employed by phages to take over the host during viral infection. Aiming to expand the available collection of phage genomes, we have isolated, sequenced, and assembled the genome sequences of four phages that infect the clinical pathogen Klebsiella pneumoniae: vB_KpnP_FBKp16, vB_… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
(61 reference statements)
0
5
0
Order By: Relevance
“… 44 Second, for RBD8_KL102, we found that 55% of the predictions pointed to bacteria from the KL38. In this case, the RBD_KL102 representative sequence showed 35% amino acid identity and 84% query coverage with the Dpo of phage φKp34, which infects KL38, 45 suggesting cross-reactivity or an evolutionary association between the abilities to infect both CLTs. Next, clusters RB64 and RBD65 were both present in phages infecting KL23, but only prophages with identity to RBD65 were found in bacteria from KL23, suggesting that the latter was the active Dpo.…”
Section: Resultsmentioning
confidence: 93%
“… 44 Second, for RBD8_KL102, we found that 55% of the predictions pointed to bacteria from the KL38. In this case, the RBD_KL102 representative sequence showed 35% amino acid identity and 84% query coverage with the Dpo of phage φKp34, which infects KL38, 45 suggesting cross-reactivity or an evolutionary association between the abilities to infect both CLTs. Next, clusters RB64 and RBD65 were both present in phages infecting KL23, but only prophages with identity to RBD65 were found in bacteria from KL23, suggesting that the latter was the active Dpo.…”
Section: Resultsmentioning
confidence: 93%
“…Rho-factor independent terminators and promoters were looked for by ARNOLD 65 and PHIRE servers 66 . The phage genome map was drawn using CGView ( http://wishart.biology.ualberta.ca/cgview/ ) and Linear Genome Plot 67 , 68 . To recognize virulence and antibiotic resistance genes, the ResFinder 4.0 and ARDB database 19 , 20 were employed.…”
Section: Methodsmentioning
confidence: 99%
“…Pseudomonas phage PAXYB1 was obtained from the Fagenbank (Delft, Netherlands). Klebsiella phage φKp18 was isolated from sewage water using K. pneumoniae L0549, a clinical isolate from UMCU, using an enrichment procedure as previously described 50 . Phage amplification was carried out by infecting the host strain (PAO1 for the Pseudomonas phages, L0549 for φKp18) overnight at 37 °C in Lysogeny Broth (LB).…”
Section: Methodsmentioning
confidence: 99%